Conjugation of Oligonucleotides to Peptide Aldehydes via a pH-Responsive N-Methoxyoxazolidine Linker - Aho Aapo; Sulkanen Mika; Korhonen Heidi; Virta Pasi (AMER CHEMICAL SOC, 2022)
The formation of N-methoxyoxazolidines in the preparation of oligonucleotide-peptide conjugates was evaluated. The reaction occurred between unprotected 2'-N-(methoxy)amino-modified oligonucleotides and peptide aldehydes in reasonable yields when isolated. The reaction is reversible under slightly acidic conditions, and it is pH-responsive. The rate and the equilibrium constant may be varied with structurally different aldehydes, allowing an optimization of the ligation and cleavage rate of the resultant conjugates. Therefore, this concept can be considered a cleavable linker.